Malnutrition assessed by mini nutritional assessment tool among Indian elderly: a systematic review and meta-analysis - Bisai, Samiran; Dey, Uposoma (International Journal Of Community Medicine And Public Health, 2020)
Overall health and nutritional status of elderly population of India is not satisfactory. Therefore, present systematic review was conducted to determine the overall occurrence of malnutrition of Indian elderly and furthermore attempted to find out the underlying causes of malnutrition. Present review considered published article reported malnutrition of elderly as assessed by mini nutritional assessment (MNA) tool. Thus, literature searching, screening and data synthesis was made and recorded following preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol. All published literature looked through utilizing the accompanying keywords. The MedCalc software was applied to estimate the overall prevalence of malnutrition by using meta-analysis statistical method. Thirty of 147 articles were included in this analysis. Overall mean MNA scores was 19.47±4.17. Study found overall prevalence of malnutrition among elderly was 17.93% (95% CI: 14.23-21.84). The prevalence of malnutrition was significantly higher in rural elderly (21.67%, 95% CI: 16.44-27.40) than urban (14.23%, 95% CI: 10.02-19.05) elderly of India. Rural elderly more likely to be 1.8 (OR: 1.76; CI: 1.56-1.99) times greater chance to be developed malnutrition than the urban elderly. Moreover, present study estimated that about 18.6 million Indian elderly population was malnourished and expected to be 22 million by 2021 due to elderly population growth, morbidity, poverty and joblessness by COVID-19 pandemic. Given the expansion of elderly malnutrition in future, there is felt need a special nutrition intervention programme for the rural elderly population. Thus, a dedicated geriatric friendly nutrition rehabilitation center (GFNRC) may be setup at every community development block of India.